Development in the Machine Learning Algorithm for the Treatment of Open Boundary Conditions in Smoothed Particle Hydrodynamics GPU Models (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Smoothed Particle Hydrodynamics (SPH) is a powerful computational method used for simulating fluid dynamics and related phenomena. One of the challenges in SPH simulations is the treatment of open boundary conditions, which are common in many real-world scenarios. Traditional approaches to handling open boundaries in SPH models involve the use of artificial boundaries or ghost particles, which can introduce inaccuracies and computational overhead. Significant advancements have been made in the application of machine learning algorithms to address the open boundary condition problem in SPH simulations. This approach leverages the power of modern Graphics Processing Units (GPUs) to accelerate the training and deployment of these algorithms. Machine learning algorithms have shown promise in accurately predicting fluid behavior near open boundaries while minimizing computational costs. This presents a comprehensive review of the latest developments in machine learning algorithms for the treatment of open boundary conditions in SPH GPU models. We discuss the key challenges associated with open boundaries in SPH simulations and how machine learning can provide efficient and accurate solutions. Various techniques, including neural networks, convolutional neural networks, and recurrent neural networks, are explored in the context of SPH simulations.  We highlight the advantages and limitations of different machine learning approaches and discuss the importance of appropriate training data and optimization strategies. The integration of machine learning algorithms with SPH simulations offers the potential to significantly enhance the accuracy and efficiency of open boundary treatments, enabling more realistic modeling of fluid dynamics in complex scenarios. We present several case studies and benchmarks that demonstrate the effectiveness of machine learning algorithms in improving open boundary conditions in SPH GPU models. We discuss the computational performance gains achieved by leveraging GPU acceleration and provide insights into the potential future directions for further research and development in this field.